The Effects of a 6-Week Controlled, Hypocaloric Ketogenic Diet, With and Without Exogenous Ketone Salts, on Body Composition Responses - Buga, Alex; Kackley, Madison L.; Crabtree, Christopher D.; Sapper, Teryn N.; Mccabe, Lauren; Fell, Brandon; LaFountain, Rich A.; Hyde, Parker N.; Martini, Emily R.; Bowman, Jessica; Pan, Yue; Scandling, Debbie; et al. (Frontiers in Nutrition, 2021)
Background: Ketogenic diets (KDs) that elevate beta-hydroxybutyrate (BHB) promote weight and fat loss. Exogenous ketones, such as ketone salts (KS), also elevate BHB concentrations with the potential to protect against muscle loss during caloric restriction. Whether augmenting ketosis with KS impacts body composition responses to a well-formulated KD remains unknown. Purpose: To explore the effects of energy-matched, hypocaloric KD feeding (<50g carbohydrates/day; 1.5 g/kg/day protein), with and without the inclusion of KS, on weight loss and body composition responses. Methods: Overweight and obese adults were provided a precisely defined hypocaloric KD (~75% of energy expenditure) for six weeks. In a double-blind manner, subjects were randomly assigned to receive ~24 g/day of a racemic BHB-salt (KD+KS; n = 12) or placebo (KD+PL; n = 13). A matched comparison group (n = 12) was separately assigned to an isoenergetic/isonitrogenous low-fat diet (LFD). Body composition parameters were assessed by dual x-ray absorptiometry and magnetic resonance imaging. Results: The KD induced nutritional ketosis (>1.0 mM capillary BHB) throughout the study (p < 0.001), with higher fasting concentrations observed in KD+KS than KD+PL for the first two weeks (p < 0.05). There were decreases in body mass, whole body fat and lean mass, mid-thigh muscle cross-sectional area, and both visceral and subcutaneous adipose tissues (p < 0.001), but no group differences between the two KDs or with the LFD. Urine nitrogen excretion was significantly higher in KD+PL than LFD (p < 0.01) and trended higher in KD+PL compared to KD+KS (p = 0.076), whereas the nitrogen excretion during KD+KS was similar to LFD (p > 0.05). Conclusion: Energy-matched hypocaloric ketogenic diets favorably affected body composition but were not further impacted by administration of an exogenous BHB-salt that augmented ketosis. The trend for less nitrogen loss with the BHB-salt, if manifested over a longer period of time, may contribute to preserved lean mass.